The Kentucky Trace : A Novel of the American Revolution - Arnow, Harriette Louisa Simpson, 1908-1986 (Book collections on Project MUSE.)
Originally released in 1974 by Knopf, The Kentucky trace is Harriette Simpson Arnow's final novel published during her lifetime. It is the story of William David Leslie Collins, raised in a Virginia gentry family of loyal British subjects, but he is covertly involved as a rebel patriot in the American Revolutionary War. Having already written in her novels Hunter's Horn and The Dollmaker about the experiences of Appalachian people who stayed home during World War II, Arnow once again describes American mountain people during wartime.